Mengenali Preferensi Minat Berkunjung Wisatawan Perempuan: Pengaruh Konten Tiktok terhadap Minat Berkunjung Wisatawan Perempuan ke Destinasi Wana Wisata Ranca Upas Bandung - Namira, Anasyah Alma; Gunadi, I Made Adhi; Nurhidayati, Hindun (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
account @vickysuuu among female tourists toward the intention to visit destination Wana Wisata Ranca Upas, Bandung. TikTok content is reviewed from three aspects, namely quality, quantity, and sender's expertise, using quantitative methods and collecting data using questionnaires and multiple linear regression analysis. The results of the study show that in terms of content, the most dominant aspects that influence respondents are the sender's expertise, followed by quality, and quantity. The three aspects simultaneously also affect the intention to visit, while partially only the sender's expertise aspect that affects to visit intention. The result can be concluded that female tourists use the sender's expertise aspect of TikTok content as the main reference in determining their intention to visit Wana Wisata Ranca Upas.